Chemical Composition and Evaluation of Anti-tyrosinase and Anti-Oxidative Effects of Topical Cream Formulation from Acacia sieberiana, Vitellaria paradoxa and Beeswax - Tamfu, Alfred Ngenge; Koudoro, Alain Yaya; Kucukaydin, Selcuk; Olaye, Theophile; Agbangnan, Pascal Dossa Cokou; Sohounhloue, Dominique Codjo Koko; Avlessi, Felicien (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Skin diseases can get natural therapies from medicinal plant-based products. In this study, a topical cream was formulated from ethanol extract of Acacia sieberiana, beeswax and Vitellaria paradoxa (shea) butter. GC-MS characterization with co-injection of the topical cream revealed Stearic acid (31.43%), Palmitic acid (23.15%), Oleic acid (21.44%) and Linoleic acid (16.20%) as the major components. Seven phenolic conpounds were identified and quantified by HPLC- DAD and Ferulic acid (12.81±0.26 mg/g) was the most abundant. The cream showed good antioxidant properties evaluated through ?-Carotene-linoleic acid assay, DPPH• radical scavenging, ABTS•+ assay, CUPRAC assay, and metal chelating assay. The cream had higher activity in the DPPH• assay (IC50 = 32.10±0.84 µg/mL), ABTS•+ assay (IC50 = 22.49±0.62 µg/mL) and CUPRAC assay (IC50 = 49.27±0.79 µg/mL) than ?-Tocopherol. The antioxidant effects are an indication that the cream can reduce oxidative stress on the skin including aging, carcinogenesis and inflammation. At 100 µg/mL, the topical cream showed tyrosinase inhibition of 48.23±0.87% regarded as relatively good compared to the standard tyrosinase inhibitor kojic acid, which showed 79.50±0.32% inhibition at the same concentration. The cosmetic cream was able to inhibit the melanin production rate-limiting enzyme, tyrosinase, indicating that it can control hyperpigmentation and skin spots.